Cenoses and species phenology of Carabid beetles (Coleoptera: Carabidae) in three stages of vegetational succession in upper Pivka karst (SW Slovenia) - Polak, Slavko (Acta entomologica slovenica (Ljubljana), 2004)
The Carabid beetle cenoses in three stages of vegetational succession in selected karst area were studied. Year-round phenology of all species present is presented. Species richness of the habitats, total number of individuals trapped and the nature conservation aspects of the vegetational succession of the karst grasslands are discussed.
Keywords: Coleoptera; fenologija; hrošči; karst; kras; krešič